2019
DOI: 10.1097/01.ogx.0000569244.48139.92
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exome Sequencing Analysis in Fetal Structural Anomalies Detected by Ultrasonography (PAGE): A Cohort Study

Abstract: Background Fetal structural anomalies, which are detected by ultrasonography, have a range of genetic causes, including chromosomal aneuploidy, copy number variations (CNVs; which are detectable by chromosomal microarrays), and pathogenic sequence variants in developmental genes. Testing for aneuploidy and CNVs is routine during the investigation of fetal structural anomalies, but there is little information on the clinical usefulness of genome-wide next-generation sequencing in the prenatal setting. We theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
130
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(139 citation statements)
references
References 23 publications
3
130
5
1
Order By: Relevance
“…The PAGE study is the largest prospective, prenatal study to date (Lancet 2019, in press), assessing the clinical utility of ES in investigation of the malformed fetus. So far, 610 trios (fetus and both parents) have been analysed in cases where fetal structural anomalies have been identified using ultrasound and where autosomal/sex aneuploidy and large copy number variants have been excluded 6. This prospective study demonstrated that prenatal ES provides up to a 8.5% additional diagnostic yield of pathological variants when compared with conventional genetic testing 6.…”
Section: Next-generation Sequencingmentioning
confidence: 89%
See 3 more Smart Citations
“…The PAGE study is the largest prospective, prenatal study to date (Lancet 2019, in press), assessing the clinical utility of ES in investigation of the malformed fetus. So far, 610 trios (fetus and both parents) have been analysed in cases where fetal structural anomalies have been identified using ultrasound and where autosomal/sex aneuploidy and large copy number variants have been excluded 6. This prospective study demonstrated that prenatal ES provides up to a 8.5% additional diagnostic yield of pathological variants when compared with conventional genetic testing 6.…”
Section: Next-generation Sequencingmentioning
confidence: 89%
“…NGS can interrogate the human genome down to the level of one base pair through either: (1) exome sequencing assessing all 20 000 gene coding regions (responsible for 85% of disease-causing variants), or by (2) WGS assessing the entire genome including introns, non-coding RNA and mitochondrial DNA in addition to assessment of copy number variation and structural rearrangements 5. In perinatology, there is growing evidence from several ‘proof of concept’ studies (eg, Prenatal Assessment of Genomes and Exomes (PAGE) study and the UK Nationwide 100,000 Genomes Project), suggesting that there is a significant additional molecular diagnostic rate through introducing NGS into mainstream clinical practice while simultaneously serving as translational studies with a proposed up and running framework for ES 6 7. It is anticipated that through NGS, the rate of diagnosis of monogenic disorders presenting with congenital anomalies will increase, as will our understanding as to why such anomalies arise during development, bringing us a step further to possible prevention 8…”
Section: Next-generation Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…Le rendement diagnostique pour la dysplasie squelettique etait de > 80 %, avec des taux de 33 a 50 % avec la consanguinit e parentale, d'importantes r egions d'homozygosit e sur une puce de polymorphisme mononucl eotidique, malformations multiples ou des fausses couches ou une mort n eonatale inexpliqu ees. L' etude britannique sur l' evaluation pr enatale des g enomes et des exomes (PAGE) a r ev el e que le rendement diagnostique etait le plus elev e chez les foetus atteints d'anomalies multisyst emes (15 %), du squelette (15 %) et cardiaques (11 %)24 . Petrovski et coll.…”
unclassified